Urgensi Bahasa Arab dalam Pendidikan Islam di Era Revolusi Industri 4.0 - Mega Primaningtyas; Cahya Edi Setyawan (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
With the presence of the Industrial Revolution 4.0, it automatically influenced the process of scientific development in Islamic education and Arabic. the development is felt in the aspects of its objectives, teaching methodology, and learning media, and competency standards of graduates who have soft skills and hard skills. Arabic, which has always been considered less important for some learners, has become an "Urgen" thing now, that is, as a door to enter the Islamic education space. The following will be explained about the influence of industrial revolution 4.0 in Islamic education and the aspects that become Urgency in Arabic as the entrance to the entry of Islamic education.